2019
DOI: 10.1111/1751-7915.13426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spray‐drying on the pili of Lactobacillus rhamnosus GG

Abstract: Summary The preservation of the viability of microorganisms in probiotic formulations is the most important parameter ensuring the adequate concentration of live microorganisms at the time of administration. The formulation and processing techniques used to produce these probiotic formulations can influence the preservation of the microbial viability. However, it is also required that the bacteria maintain their key probiotic capacities during processing, formulation and shelf life. In this study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Both studies thus highlight the feasibility for topical administration of LAB in the URT, but also pinpoint that proper selection of probiotic strains is essential. In addition to possible strain-specific effects, also other considerations should be addressed, such as the dose and formulation of the probiotic strains (Broeckx et al, 2017;Kiekens et al, 2019;Jokicevic et al, 2020). According to the definition, an 'adequate amount' of the probiotic is needed; however, the set-up of dose-response curves for probiotics is difficult (Ouwehand, 2017) and clinical studies on probiotic dose-response curves in the URT are currently lacking.…”
Section: Traditional and Advanced In Vitro Screeningmentioning
confidence: 99%
“…Both studies thus highlight the feasibility for topical administration of LAB in the URT, but also pinpoint that proper selection of probiotic strains is essential. In addition to possible strain-specific effects, also other considerations should be addressed, such as the dose and formulation of the probiotic strains (Broeckx et al, 2017;Kiekens et al, 2019;Jokicevic et al, 2020). According to the definition, an 'adequate amount' of the probiotic is needed; however, the set-up of dose-response curves for probiotics is difficult (Ouwehand, 2017) and clinical studies on probiotic dose-response curves in the URT are currently lacking.…”
Section: Traditional and Advanced In Vitro Screeningmentioning
confidence: 99%
“…Understanding strain phenomics and fluxomics with big data and machine learning may also help mastering product efficacy and stability in various applications [131]. Furthermore, beyond simple probiotic viability measures, the integrity of extracellular structures, enzymatic activities, or other effector molecules may help to assess probiotic functionality in the final application [132], provided such candidate markers are able to demonstrate a robust role in probiotic efficacy [132][133][134].…”
Section: Quality Assurance Developmentsmentioning
confidence: 99%
“…The following two large trials challenge recommendations for LGG in AGE and raise the issue of strain-specific probiotic effects 6, 8, 9 or alteration of LGG by technological processing leading to the loss of pili 10 . A multicenter Canadian RCT randomly assigned children hospitalized with AGE to probiotic treatment with a commercial mixture of L. rhamnosus and Lactobacillus helveticus versus placebo 11 .…”
Section: Diarrheamentioning
confidence: 99%
“…An MA of 23 RCTs comprising nearly 4000 patients described a reduction of AAD from 19% in placebo to 8% in probiotic-treated patients 21 . The ESPGHAN working group for probiotics/prebiotics recently questioned the practice of pooling different probiotic strains together for MAs 6 and suggested that probiotic effects against AAD may be strain-specific 22 or even depend on the probiotic preparation technique (LGG with or without pili; 10 ). Only two probiotics—LGG and S. boulardii —were tested in more than one RCT.…”
Section: Diarrheamentioning
confidence: 99%